The Influence of Human Resources Competence, Internal Control and Supervision on the Quality of Regional Financial Reports with Fraud Control Plans as Moderating Variables - Evi Ratnawati Setyaningsih; Saring Suhendro; Liza Alvia (Harmony Management: International Journal of Management Science and Business, 2025)
This research uses the Fraud Control Plan (FCP) as a moderating variable to explore how human resource competency, internal control systems, and internal supervision affect regional government financial reporting. Due to financial reporting transparency and accountability issues, public sector corruption remains rampant, prompting the study. A quantitative approach was used using moderated regression analysis. Lampung Province's Regional Financial and Asset Management Agency (BPKAD) accounting and reporting workers received questionnaires to gather data. The results show that human resource competency, internal control mechanisms, and internal supervision improve financial reporting. The Fraud Control Plan strongly moderates the correlations between human resource competency, internal supervision, and financial reporting quality, but not the internal control system. These findings imply that improving human resource competences, internal supervision, and fraud control may significantly enhance regional government financial reporting openness and accountability.